2015
DOI: 10.1542/peds.2015-1825
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Candidate Clinical Decision Rules to Identify Infants at Risk for Central Apnea

Abstract: BACKGROUND AND OBJECTIVES Central apnea complicates, and may be the presenting complaint in, bronchiolitis. Our objective was to prospectively derive candidate clinical decision rules (CDRs) to identify infants in the emergency department (ED) who are at risk for central apnea. METHODS We conducted a prospective observational study over 8 years. The primary outcome was central apnea subsequent to the initial ED visit. Infants were enrolled if they presented with central apnea or bronchiolitis. We excluded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…In a prospective observational study that included infants presented to the ED due to bronchiolitis, subsequent apnea occurred in 5% of patients. It was associated with parental report of apnea, previous history of apnea, congenital heart disease, LBW, lower weight, and age ≤6 weeks [17]. Another multicenter prospective study reported apnea in 5% of patients hospitalized with bronchiolitis [18].…”
Section: History and Physical Examinationmentioning
confidence: 95%
“…In a prospective observational study that included infants presented to the ED due to bronchiolitis, subsequent apnea occurred in 5% of patients. It was associated with parental report of apnea, previous history of apnea, congenital heart disease, LBW, lower weight, and age ≤6 weeks [17]. Another multicenter prospective study reported apnea in 5% of patients hospitalized with bronchiolitis [18].…”
Section: History and Physical Examinationmentioning
confidence: 95%
“…Apneja -komplikacija koja se javlja osobito u prematurno rođene dojenčadi i one mlađe od dva mjeseca. 65,[67][68][69][70][71][72][73] Rizik od nastanka apneje nije specifičan za određeni virusni patogen. 71,74 Apneja je značajan čimbenik rizika za zatajenje disanja i potrebu za mehaničkom ventilacijom, a njezina je pojavnost veća u dojenčadi mlađe od osam tjedana.…”
Section: Kliničke Značajkeunclassified
“…Central apnea complicates 1% of bronchiolitis and typically occurs early in the disease, when the characteristic auscultatory findings may be missed or have not manifest [8]. Infants who are at risk of central apnea, typically younger than six weeks of age, premature, or with comorbidities, may be admitted to the hospital for fear that apnea may occur when the parents are sleeping resulting in an unexpected potentially avoidable infant death [9][10][11].…”
Section: Introductionmentioning
confidence: 99%